Navigasi Digital dan Spiritualitas Remaja: Peran Pendidikan Kristen di Tengah Arus Teknologi - Maharani, Ni Kadek Putri; Boiliu, Esti Regina; Triposa, Reni (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2024)
The development of digital technology has a wide impact in various fields, including education and the formation of Christian teenagers' spirituality. Teenagers in the digital era face challenges in balancing the utilisation of technology with spiritual values. Christian education plays an important role in guiding teenagers to become wise users of technology while building spiritual maturity. The purpose of this study is to analyse the impact of digital technology on teenagers' spirituality and the role of Christian education in overcoming challenges and taking advantage of opportunities, using a qualitative method of literature study. The results showed that digital technology can support adolescents' faith development through access to spiritual resources and digital communities, but also presents challenges such as spiritual distraction and reduced face-to-face interactions. Christian education needs to integrate technology in a balanced way to preserve faith values, with an integrative approach that proposes a digital technology-based education model that not only focuses on knowledge transfer, but also on holistically developing adolescents' spiritual maturity. This model offers a new outlook in balancing the use of technology with engagement in the faith community.